REORGANISATION OF THE ARMY OF THE REPUBLIC OF SRPSKA (1995–1996) - Latinovic, Goran (Politeia, 2024)
Reorganisation of the Army of the Republic of Srpska (VRS) was caused by strategic and operational situation in the Republic of Srpska in October 1995. A proposal of reorganisation was based on an evaluation of the military situation and possible continuation of the war. The aim of reorganisation was to improve combative capacities of the VRS by its rationalisation and by enhancement of its effectiveness. There were four options of reorganisation of the VRS, and the one which advocated for creation of a large and strong brigade consisting of several light brigades instead of creation of several divisions within each corpus seemed to be the most acceptable. The Republic of Srpska did not have a demographic and economic potential for radical reorganisation of its army. However, the Dayton Peace Agreement of 21 November 1995 and its implementation created a new reality, which inevitably influenced the process of reorganisation of the VRS. By June 1996, a great majority of soldiers were demobilised and a new form of the VRS was achieved, with some additional changes taking place in December of the same year. The next reorganisation, which took place in 2002, as well as the one in 2004–2005, both under the strong pressure of the Western powers, led gradually to an annulment of the VRS and its integration in the Armed Forces of Bosnia and Herzegovina.
Keywords: The Republic of Srpska; The Army of the Republic of Srpska; Main Staff; Supreme Command; reorganization